2022
DOI: 10.1111/sum.12803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cover crops on soil hydraulic properties during commodity crop growing season

Abstract: Cover crops (CCs) can improve soil hydraulic properties prior to termination, but their effects on soil hydraulic properties during the growing season are less known. The objective of this study was to investigate the influence of no‐till CC on the soil hydraulic properties during the commodity crop growing season in Murfreesboro, USA. The CCs included hairy vetch (Vicia villosa Roth.), crimson clover (Trifolium incarnatum L.), winter wheat (Triticum aestivum L.), winter peas (Lathyrus hirsutus L.), oats (Aven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
1
0
2
Order By: Relevance
“…Therefore, during very wet growing seasons, CCs can help lengthen the growing season by increasing soil aeration. However, careful planning through species selection and appropriate termination timing is important to avoid drying out the soil (Haruna et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during very wet growing seasons, CCs can help lengthen the growing season by increasing soil aeration. However, careful planning through species selection and appropriate termination timing is important to avoid drying out the soil (Haruna et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in management practices where a rapid reduction in bulk density is required, a mixture of CCs may be more suitable as compared to a single CC species. With few studies to date concerning the influence of multi-species CCs on soil hydraulic properties (e.g., Barker et al, 2018;Singh et al, 2022;Simon et al, 2022; ) Haruna et al, 2022b), the current study could be helpful in agronomic decision making that have environmental implications.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed the impacts of cover crops that are interseeded with the annual crop (i.e., interseeded cover crop) on soil water storage and movement (Schomberg et al, 2023). However, results from some studies found that growing a winter cover crop (grown between the harvest and planting of the annual crop) resulted in higher soil water storage in the subsequent growing season of the annual crop compared with non‐cover crop treatments (Haruna et al, 2022; Leuthold et al, 2021; Rankoth et al, 2021). In addition, cover crops produce plenty of organic material, which — if left on the soil surface — can alter soil water retention due to better regulation of soil temperature and reduced surface evaporation (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%